Exposure via biotransformation: Oxazepam reaches predicted pharmacological effect levels in European perch after exposure to temazepam - Cerveny, Daniel; Fick, Jerker; Klaminder, Jonatan; Bertram, Michael G; Brodin, Tomas (Ecotoxicology and environmental safety, 2021)
It is generally expected that biotransformation and excretion of pharmaceuticals occurs similarly in fish and mammals, despite significant physiological differences. Here, we exposed European perch (Perca fluviatilis) to the benzodiazepine drug temazepam at a nominal concentration of 2 µg L-1 for 10 days. We collected samples of blood plasma, muscle, and brain in a time-dependent manner to assess its bioconcentration, biotransformation, and elimination over another 10 days of depuration in clean water. We observed rapid pharmacokinetics of temazepam during both the exposure and depuration periods. The steady state was reached within 24 h of exposure in most individuals, as was complete elimination of temazepam from tissues during depuration. Further, the biologically active metabolite oxazepam was produced via fish biotransformation, and accumulated significantly throughout the exposure period. In contrast to human patients, where a negligible amount of oxazepam is created by temazepam biotransformation, we observed a continuous increase of oxazepam concentrations in all fish tissues throughout exposure. Indeed, oxazepam accumulated more than its parent compound, did not reach a steady state during the exposure period, and was not completely eliminated even after 10 days of depuration, highlighting the importance of considering environmental hazards posed by pharmaceutical metabolites.
Keywords: Accumulation; Biotransformation; hypnotika a sedativa; oxazepam; temazepam; Hypnotics and Sedatives; zvířata; Fish; Pharmaceutical; Oxazepam; okounovití; Psychoactive drug; Metabolite; Temazepam; Perches; Metabolic transformation; Water Pollutants, Chemical; Depuration; biotransformace; Animals; chemické látky znečišťující vodu